Does Learning To Change Metter? Employee Routine, Work Intensification and Individual Performance - Damayanti, Frida Aprilia; Pujianto, Wahyu Eko (JOELS: Journal of Election and Leadership, 2024)
The purpose of this study was to analyze the effect of learning to change (LTC), employee routine (ER), work intensification (WI), and individual performance (IP) on employees of PT Sinar Murni Indoprinting. This research is quantitative research with an inferential statistical approach. This research method uses a questionnaire with 58 respondents, as a sample of a population of 58 employees using sampling techniques. Variable measurement uses a Likert scale technique with a weight scale from 1 to 5. The data analysis used is Partial Least Square (PLS). The results of this study indicate that: (1) learning to change has no effect and is not significant to individual performance. (2) learning to change has a strong and significant effect on employee routine. (3) learning to change has a strong and significant effect on work intensification. (4) employee routine has no effect and is not significant to individual performance. (5) work intensification has a strong and significant effect on individual performance.